Relationship Between Selected Physical Qualities, Bowling Kinematics, and Pace Bowling Skill in Club-Standard Cricketers. Issue 10 (October 2019) - Feros, Simon A.; Young, Warren B.; O'Brien, Brendan J.
Abstract : Abstract: Feros, SA, Young, WB, and O'Brien, BJ. Relationship between selected physical qualities, bowling kinematics, and pace bowling skill in club-standard cricketers. J Strength Cond Res 33(10): 2812–2825, 2019—Although strength and conditioning of cricket pace bowlers has become more specialized in recent times, little is understood about the interplay between physical capacities, pace bowling kinematics, and pace bowling skill measures. This study sought to determine these interrelationships. Thirty-one male club-standard pace bowlers completed 3 test sessions on separate occasions 4–7 days apart. The first testing session comprised an 8-over pace bowling assessment, where bowling skill and selected bowling kinematics were measured. A physical test battery was completed over the remaining 2 sessions. Peak and mean ball release (BR) speed were related with 1 repetition maximum pull-up strength ( r s = 0.56, p = 0.005) and correlated with 20-m sprint time ( r s = −0.42, p = 0.022; r s = −0.37, p = 0.044, respectively). Mean radial error was associated with 10-m and 20-m sprint times ( r s = 0.41, p = 0.030; r s = 0.38, p = 0.037, respectively), and correlated with height and peak power from 3 countermovement jumps (CMJs) ( r s = −0.39, p = 0.036; r s = −0.41, p = 0.031, respectively), and mean peak power from 20 CMJs ( r s = −0.45, p = 0.020). Bivariate variable error was correlated with front-leg extension angle at BR ( r s = 0.41, p = 0.036), and also with approach speed ( r s = −0.36, p = 0.050). These relationships may assist strength and conditioning coaches in designing more effective training programs to enhance bowling speed and accuracy. Training interventions are warranted, however, to validate these associations.